2016
DOI: 10.1073/pnas.1609316113
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity plays a critical role in regulating antibody-dependent cell-mediated cytotoxicity against influenza A virus

Abstract: The generation of strain-specific neutralizing antibodies against influenza A virus is known to confer potent protection against homologous infections. The majority of these antibodies bind to the hemagglutinin (HA) head domain and function by blocking the receptor binding site, preventing infection of host cells. Recently, elicitation of broadly neutralizing antibodies which target the conserved HA stalk domain has become a promising "universal" influenza virus vaccine strategy. The ability of these antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 44 publications
6
163
0
Order By: Relevance
“…The data indicate that different neutralizing and binding activities of these cAbs against different H5 strains have little influence on their ADCC activity. These paradoxical results could be explained by the recent finding that optimal activation of Fc-mediated effector functions by anti-HA antibodies requires not only Fc-Fc␥R interactions but also interactions between HA and sialic acid receptor on effector cells (36)(37)(38). Since in our previous study we found that both 65C6 and 100F4 bind and neutralize H5 viruses before and after viruses bind to target cells (27), we speculate that binding of 65C6 and 100F4 to HA probably does not interfere with the interaction between HA and the sialic acid receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data indicate that different neutralizing and binding activities of these cAbs against different H5 strains have little influence on their ADCC activity. These paradoxical results could be explained by the recent finding that optimal activation of Fc-mediated effector functions by anti-HA antibodies requires not only Fc-Fc␥R interactions but also interactions between HA and sialic acid receptor on effector cells (36)(37)(38). Since in our previous study we found that both 65C6 and 100F4 bind and neutralize H5 viruses before and after viruses bind to target cells (27), we speculate that binding of 65C6 and 100F4 to HA probably does not interfere with the interaction between HA and the sialic acid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The results of in vivo testing indicate that both Fc-Fc␥R interactions and Fc-complement interac-tions contribute to the protective effect of 1H5. More recently, it has been shown that optimal activation of Fc-mediated effector functions by anti-HA antibodies requires not only Fc-Fc␥R interactions but also interactions between HA and sialic acid receptor on effector cells (36)(37)(38). Since the requirement of the Fc-Fc␥R interactions for in vivo protection by the Abs in these studies was studied using a single-challenge virus strain and because among antihead Abs tested, 1H5 is the only Ab whose epitope was tentatively mapped to the head region outside the RBS, it remains to be determined whether the observed association between Fc-Fc␥R interactions and in vivo protection by these Abs is strain specific or epitope specific.…”
mentioning
confidence: 99%
“…Systematic comparison of the in vivo protective activity of a panel of anti-influenza mAbs with differential neutralizing potency and breadth revealed that strain-specific, neutralizing mAbs directed against the globular head of the influenza HA confer protective activity without a requirement for FcγR engagement [2931]. In contrast, broadly protective mAbs that target highly conserved influenza epitopes rely on interactions with activating Type I FcγRs to mediate antiviral activity in vivo [2933].…”
Section: Igg Fc Domain Effector Functionsmentioning
confidence: 99%
“…To a certain extent, the antibody's binding epitope can affect its ability to stimulate Fc dependent responses, presumably due to accessibility of its Fc region when bound [25]. Furthermore, the binding site of the antibody can subject it to competitive binding with other IAV antibodies in a polyclonal setting and negatively impact its ability to induce ADCC [28].…”
Section: Generation Of Neutralising Mabs Binding To the Ve Subdomainmentioning
confidence: 99%